Cardiac Autonomic Modulation and the Kinetics of Heart Rate Responses in the On- and Off-Transient during Exercise in Women with Metabolic Syndrome - Silva, Lucas R. B. E.; Zamunér, Antonio R.; Gentil, Paulo; Alves, Fagner M.; Leal, Acácia G. F.; Soares, Viviane; Silva, Maria S.; Vieira, Marcus F.; Simões, Karina; Pedrino, Gustavo R.; Rebelo, Ana C. S. (Frontiers in Physiology, 2017)
Objective: To test whether women with metabolic syndrome (MS) have impairments in the on- and off-transients during an incremental test and to study whether any of the MS components are independently associated with the observed responses. Research Design and Methods: Thirty-six women aged 35 to 55 years were divided into a group with MS (MSG, n = 19) and a control group (CG, n = 17). R-R intervals (RRi) and heart rate variability (HRV) were calculated on a beat-to-beat basis and the heart rate (HR) at the on- and off-transient were analyzed during an incremental cardiopulmonary exercise test (CPET). Results: MSG showed lower aerobic capacity and lower parasympathetic cardiac modulation at rest compared with CG. HR values in on-transient phase were significantly lower in MSG compared with CG. The exponential amplitudes “amp” and the parameters “τ” [speed of heart rate recovery (HRR)] were lower in MSG. MSG exhibited higher HR values in comparison to CG during the off-transient indicating a slower HRR. In MSG, there was an inverse and significant correlation between fasting plasma vs ΔF and glucose vs exponential “τ” of HRR dynamics. Conclusion: MS is associated with poor heart rate kinetics. The altered HR kinetics seems to be related to alterations in cardiac parasympathetic modulation, and glucose metabolism seems to be the major determinant.